Production cost analysis of Loush Bath exfoliating soap honeymon variant using the full costing method in 2025 - Santika, Nala Ratri; Gandhy, Abel; Zaini, Oktori Kiswati (Jurnal Mantik, 2026)
Pricing in micro, small, and medium enterprises (MSMEs) in the personal care sector is often based on estimates or market conventions without systematic production cost calculations, potentially resulting in prices that do not reflect the actual cost structure of the business. Previous studies have generally discussed the calculation of the Cost of Goods Sold (COGS) using the full costing method descriptively, but have not explicitly linked it to the evaluation of selling price feasibility and theoretical implications for cost-based pricing. Therefore, the gap in this study lies in the limited studies that integrate COGS calculations with an analysis of the rationality of selling prices in small-scale personal care MSMEs. This study aims to calculate COGS using the full costing method and evaluate the suitability of the selling price at Loush Bath MSME for the Honeymon variant of Exfoliating Soap. The study uses a quantitative descriptive method with a case study approach. Data were obtained through observation of the production process, structured interviews with the owner and production team, and documentation of production costs, including raw materials, direct labor, and overhead costs. The results show that the total production cost is IDR 1,628,561 with a production volume of 120 units per month, resulting in a COGS of IDR 13,571 per unit. Based on these results, the selling price of IDR 20,000 is considered economically adequate, able to cover all production costs, and provide a competitive profit margin. The originality of this study lies in the integration of full costing-based COGS calculations with the evaluation of selling price feasibility as a basis for pricing decisions in personal care MSMEs. Theoretically, this study contributes to strengthening the relevance of the cost-based pricing approach in small-scale MSMEs and confirms the role of full costing as a normative basis for rational and sustainable pricing